Quand la fiction de Jean-François Dauven flâne en Europe . À propos de Ceux qui marchent dans les villes
We intend to highlight the fictionalization of Europe in the novel Ceux qui marchent dans les villes (2009) by the contemporary Belgian Francophone writer Jean-François Dauven, This novel is based on the narrative entanglement aroused by the strolling of several characters. Their destinies meet in Lisbon, Rome, Brussels, Marseille, Prague, London, Oviedo, Seville, Paris, as well as in an imaginary city, Portosera, as many anchors, but more specifically spaces of flânerie for ten choral stories.